2017
DOI: 10.1002/2017gl075381
|View full text |Cite
|
Sign up to set email alerts
|

Mapping fluids to subduction megathrust locking and slip behavior

Abstract: In subduction zones, high fluid content and pore pressure are thought to promote aseismic creep, whereas well‐drained conditions are thought to promote locking and failure in earthquakes. However, observations directly linking fluid content and seismic coupling remain elusive. Heise et al. (2017, https://doi.org/10.1002/2017GL074641) use a magnetotelluric survey to image the electrical resistivity structure of the northern Hikurangi subduction thrust to ~30 km depth, as an indicator of interconnected fluid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Key Points: • A magnetotelluric survey was collected over the Chilean subduction zone at 36 degrees south in order to map geoelectric structure • Conductors show important dehydration reactions along plate interface as well as important zones of crustal melt beneath the volcanic arc • Correlations with previous seismic results show a possible asperity on plate interface, which may influence megathrust rupture aqueous fluids and partial melt are critical parameters in examining magma flux and magma genesis (Petrelli et al, 2018;Völker & Stipp, 2015). Furthermore, it has been widely suggested that fluids control the distribution of seismic and aseismic zones within a subduction zone and thus understanding seismicity and fluid relationships is important (Saffer, 2017).…”
Section: 1029/2018gc008167mentioning
confidence: 88%
See 1 more Smart Citation
“…Key Points: • A magnetotelluric survey was collected over the Chilean subduction zone at 36 degrees south in order to map geoelectric structure • Conductors show important dehydration reactions along plate interface as well as important zones of crustal melt beneath the volcanic arc • Correlations with previous seismic results show a possible asperity on plate interface, which may influence megathrust rupture aqueous fluids and partial melt are critical parameters in examining magma flux and magma genesis (Petrelli et al, 2018;Völker & Stipp, 2015). Furthermore, it has been widely suggested that fluids control the distribution of seismic and aseismic zones within a subduction zone and thus understanding seismicity and fluid relationships is important (Saffer, 2017).…”
Section: 1029/2018gc008167mentioning
confidence: 88%
“…Determining the amount of water, the depth at which it is released, and the zones of accumulation of aqueous fluids and partial melt are critical parameters in examining magma flux and magma genesis (Petrelli et al, ; Völker & Stipp, ). Furthermore, it has been widely suggested that fluids control the distribution of seismic and aseismic zones within a subduction zone and thus understanding seismicity and fluid relationships is important (Saffer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fault properties in subduction zones may be different from those in continental collision zones, particularly due to the availability of fluids, which may alter both the mineralogy of the downgoing sediments and the seismogenic properties of the megathrust (e.g., Saffer, 2017). Seafloor geodetic observations at subduction zones are limited due to cost and logistics, and the errors in such measurements are typically an order of magnitude larger than on land, although the rates of convergence are also typically higher (DeMets et al, 2010).…”
Section: Comparison To Observational Datamentioning
confidence: 99%
“…However, laboratory experiments found that illite shale is velocity‐strengthening/stable (Saffer & Marone, 2003), but the fluid release during the reaction has also been considered (Lauer et al, 2017; Spinelli & Saffer, 2004). In this case, earthquakes occur downdip of peak fluid release, due to lithification and increased effective stress by reduction in fluid pressure (Heise et al, 2017; Lauer et al, 2017; Saffer, 2017). Updip of the ~150 °C isotherm, pore fluid overpressure prevents seismic slip and instead promotes creep and slow slip events (Ranero et al, 2008; Saffer & Tobin, 2011; Vannucchi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%